Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan dalam Pembelian Perhiasan Emas di PT. Damai Karunia Sejahtera Kota Surabaya - Ayu Nata Utara; Handy Aribowo (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This research aims to find out more about "The Influence of Service Quality and Product Quality on Customer Satisfaction in Purchasing Gold Jewelry at PT. Damai Karunia Sejahtera City of Surabaya.” The research method used is quantitative research with a descriptive type. Data collection techniques use questionnaires and test analysis. Sampling used random sampling techniques and the number of respondents was 83 samples. The data analysis methods used in this research are Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscidality Test, Multiple Linear Regression Analysis, t Test, f Test and Coefficient of Determination. The results of this research are that service quality has a significant effect on customer satisfaction. The calculated t value for the Service Quality Variable is 0.854 and the significant value is 0.396 if t calculated < t table then Service Quality has a significant effect on Customer Satisfaction at PT. DKS. Meanwhile, the calculated t value for the Product Quality Variable is 6.662 and the significant value is 0.000 if t calculated > t table then Product Quality has a significant effect on Customer Satisfaction at PT. DKS. For R2, the value is 68.5%, the percentage value that influences the Independent Variable on the Dependent Variable. Meanwhile, the remaining 31.5% was influenced by other factors not examined in this research. Thus, all variables are influential and significant in this research.